Zwischen Dynastie, Kalifat und Scharia. Eine interdisziplinäre Betrachtung der Herrschaftslegitimation im frühneuzeitlichen Osmanischen Reich und der heutigen Türkei - Julian Ludwig Ascher (Historia.scribere)
This paper discusses types of legitimation in the Early Modern Ottoman Empire and their continuity in today’s Turkey under president Recep Tayyip Erdogan. Proceeding from a theoretical examination of the concept of legitimation, this paper shows the diversity of legitimation strategies in an interdisciplinary analysis, accentuating those that Erdogan uses to consolidate his power and bring Turkey back “to former greatness”. As will be demonstrated, Erdogan utilizes particular forms, such as religious legitimation or large-scale building projects, in order to achieve legitimacy similar to that of the Ottoman rulers.